A New Approach for Formulating Higher Education Goals in the Jordanian Tourism and Hospitality Sector - Ali Salem Musttfa Hyasat (دراسات: العلوم التربوية)
Objectives: The aim of this research is to propose a new approach for developing graduate curricula in tourism and hospitality. This approach is based on four main pillars: the needs of businesses and the market, the needs of students, the development of international standards, and the vision of secondary schools for industry.